HUBUNGAN PEMBERIAN MAGNESIUM (MgSO4) PADA KEHAMILAN PRE EKLAMASI/EKLAMASIA TERHADAP KEJADIAN ASFIKSIA PADA BBL DI RS ISLAM SAMARINDA - Saidah, Siti; Yusup, Nuuva (Jurnal Kebidanan Mutiara Mahakam, 2016)
Preeclampsia is a disease of hypertension, proteinuria and edema resulting from pregnancy. The incidence of preeclampsia in pregnant women in 2016 in Islamic Hospital Samarinda as many as 126 people and in 2016 there were 104 (41.9%) of 255 pregnant women. The purpose of this study was to determine the relationship with the incidence preeklampsia magnesium adduction in pregnant women in Islamic Hospital Samarinda 2016. This type of research is analytic with case control design in February to June 2016. The population of all pregnant women were recorded in the medical records amounted to 255 people. The total samples are 210 respondens with the proportion of cases and control 1:1. There is a relationship with the incidence of preeclampsia magnesium adduction (p=0.002). It was concluded that the magnesium levels associated with the incidence of preeclampsia.